Managing Logistic Chains on the Adriatic- Baltic Route - Igor Jakomin; Valerija Pučko (Promet - Traffic&Transportation, 1970)
Due to today's globalization and driven needs of the competitivefreight transport, as a result of the opening of new markets,the necessity for the introduction of a completely new service,such as a special container train from Koper to Gdynia,may arise unexpectedly. The adaptability of the railway operatorsto the needs of the customer, i. e. the user of the transportservice, must be available. The core of the problem of the introductionof such a new service lies mainly in the confrontationbetween the needs and requirements of the users of the transportationservices and their capabilities.